2023
DOI: 10.3389/fphys.2023.1091794
|View full text |Cite
|
Sign up to set email alerts
|

The role of class IIa histone deacetylases in regulating endothelial function

Abstract: Vascular endothelial cells (ECs) are monolayer cells located in the inner layer of the blood vessel. Endothelial function is crucial in maintaining local and systemic homeostasis and is precisely regulated by sophisticated signaling pathways and epigenetic regulation. Endothelial dysfunctions are the main factors for the pathophysiological process of cardiovascular and cerebrovascular diseases like atherosclerosis, hypertension, and stroke. In these pathologic processes, histone deacetylases (HDACs) involve in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“… 11 , 22 Moreover, although HDACis can cause anti-angiogenic effects under tumorigenic conditions, they have pro-angiogenic effects in particular tissue remodelling processes. 38 In agreement with this latter statement, vorinostat increased angiogenesis in late-stage RC injury, when new blood vessel formation is required for tissue repair. Unfortunately, the exact mechanisms through which HDACis modulate angiogenesis are not fully understood, and less is known regarding the role of the angiogenic process during RC injury progression.…”
Section: Discussionsupporting
confidence: 52%
“… 11 , 22 Moreover, although HDACis can cause anti-angiogenic effects under tumorigenic conditions, they have pro-angiogenic effects in particular tissue remodelling processes. 38 In agreement with this latter statement, vorinostat increased angiogenesis in late-stage RC injury, when new blood vessel formation is required for tissue repair. Unfortunately, the exact mechanisms through which HDACis modulate angiogenesis are not fully understood, and less is known regarding the role of the angiogenic process during RC injury progression.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, it is plausible that a selective HDAC inhibitor could offer more effective chemotherapy compared to nonselective HDAC inhibitors. Table presents a summary of recent discoveries regarding selective HDAC inhibitors and their biological mechanisms/effects in cells. Although many HDACs are highly conserved and share sequential similarity among HDAC classes such as I and IIa, HDACs play various roles for regulating epigenetics. For example, previous studies have indicated that HDAC3 is a key class I HDAC for modulating inflammatory gene expression by regulating the nuclear factor-κB (NF-κB) pathway .…”
Section: Histone Deacetylases (Hdacs) and Hdac Inhibitorsmentioning
confidence: 99%
“…Although several reviews have reported the synthesis methodologies, binding thermodynamics, and clinical drug development of HDAC inhibitors, [18][19][20][21][22][23][24]26,27 to the best of our knowledge, the importance of the optimization of binding kinetic parameters for developing potent in vivo isoform-selective HDAC inhibitors has rarely been mentioned. Therefore, this Perspective focuses on the development of kinetically isoform-selective slowbinding HDAC inhibitors, especially their binding kinetics and action mechanisms, to highlight the impact of kinetic 33,34 anticancer activity inhibiting the ERK1/2 signaling pathway inducing the recruitment and differentiation of highly phagocytic and stimulatory macrophages within tumors abolishing NO-induced formation of macromolecular complexes anti-inflammatory activity reducing pulmonary arterial hypertension and cerebral ischemia/reperfusion injury suppression of myocyte hypertrophy immunostimulatory activity decreasing downstream hypoxia-inducible factor (HIF)-VEGF signaling class IIb 29,35,36 49 Benzamide HDAC inhibitors were initially considered weak inhibitors, owing to their high IC 50 for HDACs. However, cell-based and mouse models revealed that benzamide HDAC inhibitors have unique biological functions, outstanding subtoxic efficacies, and effective deacetylase IC 50 values for Friedreich's ataxia (FRDA) and Huntington's disease.…”
Section: Slow-binding Hdac Inhibitorsmentioning
confidence: 99%
“…Class IIa HDACs exhibit unique features compared with to the other HDAC classes. They have a C‐terminal deacetylation domain, a sequence for nuclear export, as well as an N‐terminal myocyte enhancer factor 2 (MEF2) domain (Shen et al, 2023 ). HDAC4, belonging to Class IIa, is one of the largest isozymes in the HDAC family, with an approximate molecular weight of 120 kDa and a length ranging from 972 to 1084 amino acids depending on splicing.…”
Section: Introductionmentioning
confidence: 99%